Successful Chemotherapy of Canine Transmissible Venereal Tumor in a Bitch - Parmar, K.H.; Joseph, Joice P.; Morabiya, K.K.; Thakre, B.J.; Patel , J.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Transmissible venereal tumor (TVT), also referred to as Sticker’s tumor, venereal granuloma, transmissible venereal sarcoma, infective venereal tumor, and transplantable lymphosarcoma, is a tumor that primarily affects the genitalia of sexually mature dogs, and is usually transmitted during coitus (Rogers, 1997). In India, it is the most common tumor of dogs owing to uncontrolled breeding practices (Singh et al., 1991). The transmissible nature is suggestive of an infectious etiology; however, no infectious particles have ever been detected within the tumor cells (Rogers, 1997). These tumor cells are not the patient’s own cells transformed into cancer cells. The TVT is a tumor that grafts itself from one dog’s body onto another dog’s body (Richardson, 1981). The present communication reports a case of TVT and its successful chemotherapeutic management in a bitch.